1993
DOI: 10.1021/bi00053a037
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydrazine to release in intact and unreduced form both N- and O-linked oligosaccharides from glycoproteins

Abstract: The use of hydrazine to release unreduced N- and O-linked oligosaccharides from glycoproteins has been investigated using several "standard" glycoproteins of previously defined glycosylation. It is shown that hydrazinolysis can be used to release intact N- and O-linked oligosaccharides in an unreduced form. The release of O-linked oligosaccharides occurs with a lower temperature dependence than the release of N-linked oligosaccharides, and the kinetic parameters governing release of oligosaccharides from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(230 citation statements)
references
References 38 publications
2
223
1
1
Order By: Relevance
“…N-linked glycans were released by large scale hydrazinolysis followed by reacetylation [39,40] from the well-characterized glycoproteins (Sigma Chemical Co. Ltd., Poole, Dorset, UK) ribonuclease B [41], porcine thyroglobulin [42,43], chicken ovalbumin [44,45], and bovine fetuin [46]. Methanol was obtained from BDH Ltd. (Poole, UK) and the various inorganic salts were from Aldrich Chemical Co. Ltd. (Poole, UK) and BDH.…”
Section: Methodsmentioning
confidence: 99%
“…N-linked glycans were released by large scale hydrazinolysis followed by reacetylation [39,40] from the well-characterized glycoproteins (Sigma Chemical Co. Ltd., Poole, Dorset, UK) ribonuclease B [41], porcine thyroglobulin [42,43], chicken ovalbumin [44,45], and bovine fetuin [46]. Methanol was obtained from BDH Ltd. (Poole, UK) and the various inorganic salts were from Aldrich Chemical Co. Ltd. (Poole, UK) and BDH.…”
Section: Methodsmentioning
confidence: 99%
“…This method has worked well in our hands. Other methods, including gel reductive b-elimination, have been described [16][17][18][19] .…”
Section: Release Of Glycansmentioning
confidence: 99%
“…N-Linked glycans were released from glycoproteins by hydrazinolysis. 34 Briefly, anhydrous hydrazine was added to dried glycoprotein samples, heated to 100 °C for 6 h, and then evaporated under a nitrogen stream. The bulk sample was re-N-acetylated in saturated sodium bicarbonate with acetic anhydride, desalted on Dowex 50W cation-exchange resin, and purified by cellulose column chromatography 18 (slurry packed with medium fibrous cellulose in 1-butanol/ethanol/water, 4:1:1).…”
Section: Sample Preparationmentioning
confidence: 99%
“…6 In both cases, however, the product structures remain to be characterized. A large body of work has shown that spectral comparisons of isomers at different stages of sequential molecular fragmentation (MS n ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are clearly different, although in one case, reproducibility has been reported to be "vague". 25 In our experience, spectral reproducibility has been excellent, 26 and this very feature has provided an opportunity to build a searchable fragment library 27 and derive glycan structure with supporting tools.…”
mentioning
confidence: 99%